Mekaar Program Evaluation in Micro-enterprises Development for Underprivileged Women in Kutasari, Baturraden District - Irma Zahidah; Herman Sambodo; Bambang Bambang (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2022)
Abstract This research was conducted in the Kutasari Village, Baturraden District, Banyumas Regency, Central Java Province. The purpose of this study to analyze (1) The accuracy of the Mekaar program in achieving its targets, (2) The characteristics of the Mekaar program's policies in giving an impact on underprivileged women micro-entrepreneurs in Kutasari Village, Baturraden District (Pro-poor, progressive or regressive), (3) The effectiveness of the Â Mekaar Program in Kutasari Village, Baturraden District, (4) Measuring the difference in income of women micro-entrepreneurs in Kutasari Village, Baturraden District before and after receiving Mekaar financing. The number of respondents consisted of 30 underprivileged women. This research uses primary data, which were collected using the method of observation, interviews and questionnaires. The data obtained were then analyzed using data proportion techniques, Benefit Incidence Analysis (BIA), Appraisal Effectiveness Program and Wilcoxon Test. Based on the research results, the following conclusions can be drawn: (1) Mekaar Program in Kutasari Village, Baturraden District is right on target, (2) Mekaar Program in Kutasari Village, Baturraden District is Pro-poor, (3) Mekaar Program in Kutasari Village, Baturraden District is classified as effective, (4) There is a difference between operating income before and after obtaining Mekaar financing.Â Keywords: Underprivileged Women, Mekaar, Benefit Incidence